Trend analysis of hydroclimatic variables of the Coast of Chiapas - Escalante-Sandoval, Carlos; Amores-Rovelo, Leonardo (Revista Mexicana de Ciencias Agrícolas, 2018)
The region called Chiapas Coast has been affected by some periods of drought and floods, which have caused serious economic and social damage. It was considered to deforestation as the main cause of this. However, we consider the spatial and temporal variation of hydroclimatic variables. For this purpose it has been collected the information of rainfall, maximum and minimum temperature of 51 weather stations for the period 1960-2010 and 12 runoff gauging stations for the period 1964-2005. The trend analysis of annual time series (agricultural year) and seasonal (spring-summer and autumn-winter) of precipitation, maximum temperature, minimum temperature, evapotranspiration and runoff, performed with the nonparametric statistical test Mann- Kendall. It was found that most of the Chiapas Coast presents trends in the series. These results should be taken into account to take protective measures against the most persistent occurrence of pluvial and f luvial f looding and mitigation measures against the increase in maximum temperatures that affect the health of living beings, and evapotranspiration increases the demand for water in agriculture.
Keywords: time series; Mann-Kendall; climate variability